Autonomous ground vehicles in urban last-mile delivery : an exploration of the implementation feasibility and consumer’s acceptance - Barthuly, Daniel (2020)
E-Commerce has rapidly changed the urban last-mile delivery in recent years, and Courier-, Express- and Parcel (CEP) companies are challenged by the increasing demand. Service robotics with autonomous vehicles are subject to be the catalyst for transforming the industry. Considering the infancy and lack of research on the subject, the purpose of this study is to explore the concept of autonomous ground vehicles (AGVs) in urban last-mile delivery from two perspectives. First, data about the industry and insights from the technology provider summarize the status quo of recent developments and implementation barriers with the help of expert interviews. The findings show obstacles in the technological maturity and regulatory framework. Moreover, although only road-AGVs (rAGVs) will significantly change the industry, sidewalk-AGVs (sAGVs) act as a proof of concept as the implementation is more feasible. In addition, they create new premium services for the consumers. Second, an attempt to determine the consumer’s acceptance of sAGVs, using the combination of the technology acceptance model and the technology readiness index, is made with an online survey. The proposed research model is analysed by means of simple regression analysis, and all hypotheses are supported. The majority of the respondents have a positive attitude towards the concept of sAGVs for delivery and consider using it when the safety of their delivery goods is guaranteed. This dissertation enriches the literature on human-robot acceptance as well as the management of CEP-companies to increase the engagement in the implementation of sidewalk-AGVs to increase service innovation for consumers.